Heroes of Light - A Serious Game Development Journey for Basic Life Support Education - Mendes, Ingrid Nery (2024)
This work discusses the importance of games, especially the kind of serious games, in the assimilation and reinforcement of specific knowledge, such as Basic Life Support (BLS). It highlights the need for regular practice to maintain this knowledge, especially among nursing students, first responders and other healthcare professionals. A software prototype was developed to address this memory gap, using game mechanics to encourage consistent BLS practice. The project followed the guidelines established by the Games and Health research group, from Fundação Oswaldo Cruz do Brasil, resulting in the creation of a digital prototype using the Ren'Py engine, chosen for its narrative emphasis, which makes use of the Python programming language, with low implementation complexity and cost.